Hospitalization and Life Support before Liver Transplantation – Easily available Predictors for Post-Transplant Patient Survival. (July 2018) - Wiering, Leke; Ritschl, Paul; Hippler-Benscheidt, Michael; Aigner, Felix; Biebl, Matthias; Eurich, Dennis; Schmelzle, Moritz; Sauer, Igor; Kotsch, Katja; Pratschke, Johann; Öllinger, Robert
Abstract : Introduction: Currently liver allocation is based on urgency in many countries, mostly represented by the MELD score. In contrast to allocation of other organs, e.g. lung, survival benefit is not included and to date no applicable outcome predictors have been implemented for liver allocation. Aim of this study was to analyze the prognostic value of hospitalization prior transplantation (Tx), pre-operative life support and the duration thereof for transplant outcome. Materials and Methods: The electronic record system of the Charité - Berlin, Germany, was analyzed retrospectively for all patients who underwent liver Tx from 2005 to 2016 for hospitalization and life support before Tx. Life support was defined as dialysis accordingly to ET Liver Allocation system, mechanical ventilation and need of catecholamines. Results and Discussion: From 1244 liver transplant recipients in this era, 264 underwent Tx coming from an intensive care unit (ICU), 178 patients from a regular ward and 802 from home. Of all recipients 187 required dialysis, 123 ventilation and 101 were under catecholamine therapy. Patients coming from the ICU were significantly younger but sicker according to their higher labMELD at day of Tx. Not surprisingly these patients had a significant lower 3 months, 1 year and 3 year survival compared to patients coming from home (ICU vs. home; 76, 9% vs. 94, 4% and 65, 9% vs. 87, 5% and 64, 4% vs. 82, 4%; all p=0, 000). Interestingly differences between patients from the ICU and a regular ward showed no significance, not even for short term survival (3 month: 76, 9% vs. 84, 3%; p=0, 057), decreased over time and did not have an influence on 1- and 3 year survival (1 year: 65, 9% vs. 71, 9%; p=0, 132; 3 year: 64, 4% vs. 65, 2%; p=0, 556). Subgroup analysis revealed that the length of ICU stay prior to Tx had a significant impact on patient survival if longer than 6 days (1-6 days vs. 7-14 days; 1 year p=0, 036). Remarkably no changes between 7-14 days or >14 days could be noticed (p=0, 469). Dialysis prior to Tx was associated with an inferior outcome compared to patients without renal placement (3 year: 56, 1% vs. 79, 7% p=0, 000). These results remained significant even for patients receiving only dialysis and no other life support therapy whereas ventilation or catecholamines alone did not influence survival. There were no significant differences between the pre-operative labMELD of these three groups. However, recipients with ventilation and catecholamines showed similar results as patient with dialysis only (3 year: 61, 3% vs. 60, 6% p=0, 890). Patients with the triad of dialysis, ventilation and vasopressor therapy had the worst outcome with a 3 year patient survival of only 47, 4% compared to 80% of patients without life support (p=0, 000). Conclusion: Hospitalization status as well as life support before Tx are valuable predictors for patient survival following liver Tx and should be considered for the allocation process.